Atributos do solo e flora infestante em sistema de semeadura direta do milho na palha de leguminosas arbóreas - Macêdo, Jeane Rodrigues de Abreu [UNESP] (2015)
The objective of this study was to evaluate the effect of different combinations of legumes tree in alleys cropping systems with four years on the chemical and physical properties of the soil, and the diversity and dynamics of weed population. The experiment consisted of five treatments with eight replications in a randomized block experimental design: Leucaena leucocephala + Clitoria fairchildiana, L. leucocephala + Acacia mangium, Gliricídia sepium + C. fairchildiana, G. sepium + A. mangium and control (without legumes). The following soil properties were evaluated: organic matter, pH in CaCl2, P, K, Ca, Mg, H + Al, Na, Al, density, porosity and stability of aggregates and calculated the sum of bases (SB), the cation exchange capacity (CEC) and base saturation (V%). The weeds were evaluated for: family, species, number of individuals and biomass and estimated abundance, frequency, dominance and the Importance Value Index (IVI). The floristic diversity was analyzed using the diversity index of Shannon-Wiener (H '). At depth 0-10 cm all treatments affected magnesium concentration. For density and porosity of the soil there were no significant differences between treatments. For the aggregate stability, the values for mean weight diameter (MWD) varied between treatments in the 10-20 cm layer, the combinations L. leucocephala + A. mangium and G. sepium + A. mangium presented the highest values. Thirty two plant species belonging to sixteen families were identified. The most representative families were Poaceae, with six species, followed by Cyperaceae and Malvaceae, with four species. The specie Cyperus lanceolatus presented the highest IVI. Leucaena leucocephala + Clitoria fairchildiana and Gliricidia sepium + Acacia mangium presented greater diversity. Regarding the biomass of weeds, there were differences between treatments with the highest value observed for the control treatment. There were no significant differences between ...